Remembering communism - making sense of post-communism. An analysis of discursive strategies in Lithuanian textbooks - Christophe, Barbara (Georg-Eckert-Institut für Internationale Schulbuchforschung, 2010)
In the following paper I will present some preliminary thoughts I have developed during one year of research on post-soviet history teachers and their role as an interface between individual and collective memory of the communist past.

Der Artikel präsentiert einleitende Überlegungen, die die Autorin während ihrer einjährigen Forschung über post-sovietische Geschichtslehrer und deren Rolle als Vermittler zwischen persönlischer und kollektiver Erinnerung an die kommunistische Vergangenheit entwickelt hat.
Kostenfreier Zugang. - Lizenz: creative commons: by-nc-nd
Keywords: Litauen; Kommunismus, Motiv; Geschichtsbewusstsein; Geschichtsdarstellung; Geschichtsunterricht; Schulbuch